Proposed Scoring System for Evaluating Clinico-radiological Severity of COVID- 19 using Plain Chest X- ray (CXR) changes (CO X-RADS): Preliminary results: Scoring chest X-ray and Covid-19 - De Sanctis, Vincenzo; Bedair, Elsaid M.A; Soliman, Ashraf T; Nair, Arun Prabhakaran; Al Masalamani , Muna A.; Yassin, Mohamed (Acta Biomedica Atenei Parmensis, 2020)
Summary. Background: Plain chest radiograph (CXR), although less sensitive than chest CT, is usually the first-line imaging modality used for patients with symptomatic SARS-CoV-2 infection. The relation between radiological changes in CXR and clinical severity of the disease in symptomatic patients with COVID 19 has not been fully studied and there is no scoring system for the severity of the lung involvement, using the plain CXR. Aim of the study: Current COVID-19 radiological literature is dominated by CT and a detailed description CXR appearances in relation to the disease time course is lacking. We propose an easy scoring system (CO X-RADS) to describe the severity of chest involvement in symptomatic COVID 19 patients using CXR and to correlate the radiological changes with the clinical severity of the disease. Patients and methods: The clinical manifestations and CXR findings were recorded in 500 symptomatic COVID-19 positive patients who were admitted to Hamad Medical Corporation (HMC) COVID-19 designated facility Center from January to June 2020. The severity and outcome of the disease included: intensive care unit admission, need for oxygen therapy, mechanical ventilation. and mortality rate. Results: Most of our symptomatic patients (86.8%) had mild and moderate clinical manifestations. The remaining 13.2% had severe manifestations, including: fever, persistent dry cough, shortness of breath, dyspnea, abdominal and generalized body pains. Based on our radiological scoring system (0 to 10) patients were distributed according to their CXR findings into different categories and according to our suggested (CO X-RADS) severity system into five categories (0 to IV). Patients with mild clinical manifestations showed low scoring in CXR (score 0 up to 4) and they represented 72% of our patients. Patients with moderately severe clinical manifestations showed mainly GGO (scoring 5 and 6) and represented about 14.8% of patients. Patients presented with severe clinical manifestations had obvious lung consolidations at the time of presentation with CXR scoring system ≥ 7 and represented about 13.2% of patients. Conclusion: We proposed a simple CXR reporting scoring system (CO X-RADS) to categorize COVID-19 patients according to their radiological severity. This radiological score was correlated well with the clinical severity score of patients. We encourage other centers to test this scoring system in correlation with the clinical status of patients.